Islamic Religious Education in Shaping Student Character amid Digital-Era Challenges: A Qualitative Study at MTs Al-Khairat, Ternate - Alifyah Jufri; Aldarisma Isnain; Reva Revina Alzahra; Nursiami Karim; Rifan Larudi; M. Irsyad Irwan (Manunggal Halim Jaya, 2026)
This study examines how Islamic religious education contributes to the formation of student character in the digital era and identifies the strategies teachers use to address the character-related problems that emerge in this context. The study employs a qualitative descriptive approach, with data collected through classroom observation, semi-structured interviews with teachers and students, and documentation, at MTs Al-Khairat, Ternate City. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing, with credibility strengthened through source and method triangulation. The results show that students face several character-related problems, including low confidence in public speaking, limited interest in religious learning, and overdependence on digital technology and artificial intelligence tools that weakens critical thinking and academic honesty. Teachers respond to these problems mainly through personal approaches, exemplary conduct, and habituation of religious practice, which observational data associate with improvements in student discipline, religious engagement, and manners. The findings suggest that Islamic religious education functions most effectively as a character-formation vehicle when exemplary teaching is combined with consistent habituation and collaboration between school, family, and community.